2015
DOI: 10.1016/j.mce.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Multiple exportins influence thyroid hormone receptor localization

Abstract: The thyroid hormone receptor (TR) undergoes nucleocytoplasmic shuttling and regulates target genes involved in metabolism and development. Previously, we showed that TR follows a CRM1/calreticulin-mediated nuclear export pathway. However, two lines of evidence suggest TR also follows another pathway: export is only partially blocked by leptomycin B (LMB), a CRM1-specific inhibitor; and we identified nuclear export signals in TR that are LMB-resistant. To determine whether other exportins are involved in TR shu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…No role has yet been reported for these karyopherins, or for transportins 1 and 2 (Twyffels et al, 2014), in import of nuclear receptors, so they were considered less likely candidates. In a separate study focused on TRα1 nuclear export pathways, we confirmed that transportins 1 and 2 are not involved in nuclear import (or export) of TRα1 (Subramanian et al, 2015). …”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…No role has yet been reported for these karyopherins, or for transportins 1 and 2 (Twyffels et al, 2014), in import of nuclear receptors, so they were considered less likely candidates. In a separate study focused on TRα1 nuclear export pathways, we confirmed that transportins 1 and 2 are not involved in nuclear import (or export) of TRα1 (Subramanian et al, 2015). …”
Section: Resultssupporting
confidence: 60%
“…Twenty six hours post-transfection, HeLa cell protein lysates were prepared and analyzed by immunoblotting as described (Subramanian et al, 2015). Antibodies were used with the following concentrations: anti-GAPDH (Santa Cruz Biotechnology Inc, Dallas, TX), 1:5000; anti-importin β1 (Santa Cruz), 1:2000; anti-importin 4 (Santa Cruz), 1:333; anti-importin 5 (Santa Cruz), 1:10,000; anti-importin 7 (Abcam, Cambridge, MA), 1:1000; anti-importin 8 (Abcam), 1:250; anti-importin 9 (Abcam), 1:250; anti-importin 11 (Abcam), 1:333; anti-importin 13 (Santa Cruz), 1:100; anti-importin α1 (Santa Cruz), 1:2000; anti-importin α3 (Thermo Scientific), 0.2 μg/ml; horseradish peroxidase (HRP)-conjugated donkey anti-rabbit IgG (GE Healthcare Life Sciences), 1:25,000; HRP-sheep anti-mouse IgG (GE Healthcare Life Sciences), 1:25,000; or HRP-mouse anti-goat IgG (Santa Cruz Biotechnology), 1:25,000.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly intriguing since our prior studies have shown that AF‐2 overlaps with one of TR's nuclear export signals, NES‐H12 (see Figure A). Previously, we used RNA interference‐mediated knockdown to show that exportin 4, 5, and 7 influence TRα1 localization, suggesting these exportins are candidates for mediating TRα1 nuclear export, in combination with the previously characterized CRM1/calreticulin pathway . To determine whether these exportins influence localization via direct protein‐protein interactions, we performed coimmunoprecipitation assays.…”
Section: Resultsmentioning
confidence: 99%
“…mCherry‐tagged TRα1, TRβ1, and v‐ErbA expression plasmids were prepared by subcloning the corresponding coding regions from GFP‐TRα1, GFP‐v‐ErbA, and GFP‐TRβ1 into pmCherry‐C1 (Clontech). GFP‐GST‐GFP‐Hinge, containing NLS‐1 of TRα1, and GFP‐GST‐GFP‐Hinge‐LBD were previously described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation